Reconstruction of Moral Education Based on Sustainable Religious Education in The Perspective of Education in The 21st Century - Suyahman, Suyahman (Proceeding International Conference on Religion, Science and Education, 2023)
The aim is to describe building sustainable religious education-based moral education in the perspective of 21st century education and describe the steps that must be taken. The type of research is qualitative research with a case study approach, data collection methods: observation, interviews and documentation, validity is carried out by triangulation of methods and sources, data analysis techniques using interactive analysis techniques flow consisting of 3 stages, namely: data reduction, data display and data verification. The results of the study: the results of observations in the field show that there are many immoral attitudes, behaviors, and actions including: promiscuity, free sex, open promiscuity, open and legal places of immorality, loss of shame and so on. The results of interviews with community leaders, religious leaders, traditional leaders and youth leaders obtained information: a lack of exemplary behavior in the family, in the community and carried out by community leaders, religious leaders, traditional leaders and youth leaders who went viral on social media. The lack of maximum giving of good habituation in the family, community environment, community leaders, religious leaders, traditional leaders and youth leaders. Challenges and opportunities for 21st century education that prioritize the use of IT, education based on global information openness, learner-centered education as well as education that is interesting, challenging and fun for students, and child-friendly education. In conclusion: building moral education based on sustainable religious education in the perspective of 21st century education must be carried out continuously by empowering all existing components and adapted to the demands of the current era. Moral education must be built cybergistically with religious principles, religious education becomes a filter for moral education in line with the demands of the essence, urgency and substance of 21st century education.